2013
DOI: 10.1021/ja4076748
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Nanostructured “Black” Rutile Titania as Excellent Catalyst for Hydrogen Production Enhanced by Sulfur Doping

Abstract: Modification of rutile titanium dioxide (TiO2) for hydrogen generation and water cleaning is a grand challenge due to the chemical inertness of rutile, while such inertness is a desired merit for its stability in photoelectrochemical applications. Herein, we report an innovative two-step method to prepare a core-shell nanostructured S-doped rutile TiO2 (R'-TiO2-S). This modified black rutile TiO2 sample exhibits remarkably enhanced absorption in visible and near-infrared regions and efficient charge separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
286
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(303 citation statements)
references
References 38 publications
15
286
0
2
Order By: Relevance
“…However, the HRTEM images of TiO 2 -N and Au-TiO 2 -N show no obvious disordered shell near the surface region (Figure 3e,f). Thus, the results indicate that H 2 atmosphere resulted in the surface structure rearrangement and disordered shell, in agreement with the reported results [47,49] As shown in Figure 3a,d, TiO2−x-N and TiO2-N supports were decorated with Au particles (dark dots). The surface-averaged Au cluster diameters (dTEM) of Au-TiO2−x-N and Au-TiO2-N are 9.1 nm and 7.5 nm, respectively (Figure 3g,h).…”
Section: Structural Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…However, the HRTEM images of TiO 2 -N and Au-TiO 2 -N show no obvious disordered shell near the surface region (Figure 3e,f). Thus, the results indicate that H 2 atmosphere resulted in the surface structure rearrangement and disordered shell, in agreement with the reported results [47,49] As shown in Figure 3a,d, TiO2−x-N and TiO2-N supports were decorated with Au particles (dark dots). The surface-averaged Au cluster diameters (dTEM) of Au-TiO2−x-N and Au-TiO2-N are 9.1 nm and 7.5 nm, respectively (Figure 3g,h).…”
Section: Structural Propertiessupporting
confidence: 92%
“…However, the HRTEM images of TiO2-N and Au-TiO2-N show no obvious disordered shell near the surface region (Figure 3e,f). Thus, the results indicate that H2 atmosphere resulted in the surface structure rearrangement and disordered shell, in agreement with the reported results [47,49], so the calcination in H2 atmosphere was chosen as the hydrogen-etching technology. Furthermore, the evolution of surface structure was also confirmed by the H2-TPR results ( Figure 3i).…”
Section: Structural Propertiessupporting
confidence: 87%
“…Disordered TiO 2 : Black TiO 2 was synthesized by hydrogenation process for greatly shifting the top edge of valence band of white TiO 2 , drastically narrowing its band gap and thus displaying strong absorption in visible and infrared regime 36. Naldoni et al reported the band gap narrowing of black TiO 2 nanoparticles (crystalline core and disordered shell) in the co‐presence of surface disorder and oxygen vacancies.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…Self-doping with Ti 3 þ was further developed for narrowing the band of TiO 2 without the introduction of unwanted carrier recombination centres from dopants [19][20][21] , which consequently exhibited good stability and considerable activity for photocatalytic hydrogen production under visible light 20,21 . Recently, hydrogenation of crystalline TiO 2 was disclosed as a new approach to enhance the visible as well as infrared light absorption of pristine TiO 2 and subsequently triggered great interest [22][23][24][25][26][27][28] . The surface disorder of hydrogenated black TiO 2 , instead of bulk Ti 3 þ , was proposed to be responsible for the extended light absorption 23,24 .…”
mentioning
confidence: 99%